A prepolymerization process for a solid catalyst component for the polymerization of olefins and use thereof
Patent Information
- Application Number
- CN202311309269.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-10-10
AI Technical Summary
[0006]本发明的目的是提供一种用于烯烃聚合的固体催化剂组分的预聚合方法及其应用,本发明的固体催化剂组分经过特殊方法的预聚,通过改变活性中心的组成、结构,克服现有以式(Ⅰ)所示化合物为内给电子体催化剂氢调敏感性不足的难题,可以进一步提高催化剂的氢调敏感性,同时催化剂合成的聚合物具有较高的堆密度
[0030]本发明所述催化剂采用特定的含镁载体,在经过特殊方法预聚后,可以提高催化剂的氢调敏感性,同时催化剂合成的聚合物具有较高的堆密度,而且产品分子量分布更宽,有利于提高产品的加工性能。
Smart Images

Figure CN119798489B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of olefin polymerization catalysts, and more specifically to a prepolymerization method for a solid catalyst component used in olefin polymerization and its application. Background Technology
[0002] As one of the five major synthetic resins, polypropylene resin has wide applications in industrial and daily life due to its excellent performance characteristics. Since the discovery of Ziegler-Natta catalysts in the last century, its production capacity and output have been continuously improving, especially in the last decade or so, experiencing rapid development. The driving force behind this rapid development lies in the continuous upgrading of catalyst technology and processing technology. Catalyst technology is the core technology behind this development. The support is the cornerstone of Ziegler-Natta catalysts, determining the morphology and performance of the catalyst.
[0003] Only spherical catalysts can yield spherical polymers, which have good flowability. This type of catalyst is commonly used in industrial loop-type polypropylene processes. Similarly, only spherical supports can produce spherical catalysts. For example, CN201610881057.6 discloses a novel support preparation method: synthesizing spherical supports using magnesium chloride, alcohols, and epoxides. However, spherical catalysts may break during industrial polypropylene production, preventing the formation of spherical polymers. Therefore, prepolymerization is necessary to ultimately obtain spherical polymers. Furthermore, polymer particle breakage still occurs during polypropylene production, resulting in a high content of fine powder in the polymer. Therefore, many companies and research institutions have conducted research on prepolymerization.
[0004] For example, US9453088B2 discloses a method for prepolymerizing an olefin by contacting it with a catalyst to obtain a prepolymerization catalyst with an activity factor of less than 50 times. For example, US7329714B2 discloses a method for prepolymerization using propylene or 4-methyl-1-pentene.
[0005] The purpose of these prepolymerization catalysts is to reduce breakage and thus reduce the fine powder content in the final polymer, but they still have the problem of insufficient hydrogen sensitivity. Summary of the Invention
[0006] The purpose of this invention is to provide a prepolymerization method for a solid catalyst component for olefin polymerization and its application. The solid catalyst component of this invention is prepolymerized by a special method. By changing the composition and structure of the active center, it overcomes the problem of insufficient hydrogen sensitivity of existing catalysts with the compound shown in formula (I) as the internal electron donor. It can further improve the hydrogen sensitivity of the catalyst, and the polymer synthesized by the catalyst has a high bulk density.
[0007] According to a first aspect of the present invention, the present invention provides a method for prepolymerizing a solid catalyst component, comprising:
[0008] (1) In the presence of an inert solvent, catalyst component A, alkylaluminum and external electron donor compound are brought into contact and reacted; wherein catalyst component A contains titanium, magnesium, halogen and internal electron donor compound;
[0009] The internal electron donor compounds include compounds of the class shown in formula (I);
[0010]
[0011] In equation (Ⅰ), R”'1 and R”'2 may be the same or different, and each is independently H, C1~C 14 Straight-chain alkyl groups, C3-C 14 Branched alkyl groups, C3-C 10 cycloalkyl, C6-C 10 aryl, C7~C 10 alkylaryl or C7~C 10 Aryl groups;
[0012] R”'3 and R”'4 may be the same or different, and each can be independently represented as C1 to C2. 14 Straight-chain alkyl groups, C3-C 14 Branched alkyl groups, C3-C 10 cycloalkyl, C6-C 10 aryl, C7~C 10 alkylaryl or C7~C 10 Aryl groups;
[0013] The magnesium element is derived from a magnesium-containing carrier, which includes the magnesium compound shown in formula (II);
[0014]
[0015] In formula (II), R1 is a straight-chain or branched alkyl group of C1 to C8, or a cycloalkyl group of C3 to C8;
[0016] R2 and R3 may be the same or different, and each is independently hydrogen or a straight-chain or branched alkyl group of C1 to C5, wherein the hydrogen on the alkyl group may optionally be replaced by a halogen atom; X is a halogen, preferably chlorine or bromine; m is 0.1 to 1.9, n is 0.1 to 1.9, and m+n=2;
[0017] (2) Add α-olefins to the reaction system obtained in step (1) to carry out a polymerization reaction;
[0018] (3) Remove the unreacted α-olefin from step (2) and add hydrogen to the reaction system obtained in step (2) to carry out the reaction.
[0019] Optionally, the mass ratio of the α-olefin to catalyst component A is 0.04:1 to 10:1, and the amount of hydrogen added is controlled to maintain the reaction pressure at 0.01 to 1.0 MPa.
[0020] According to a second aspect of the present invention, a solid catalyst component prepared by the prepolymerization method described in the first aspect of the present invention is provided. The solid catalyst component comprises magnesium, titanium, halogens, polyα-olefins, and an internal electron donor compound, wherein the internal electron donor compound comprises a compound of formula (I).
[0021]
[0022] In equation (Ⅰ), R”'1 and R”'2 may be the same or different, and each is independently H, C1~C 14 Straight-chain alkyl groups, C3-C 14 Branched alkyl groups, C3-C 10 cycloalkyl, C6-C 10 aryl, C7~C 10 alkylaryl or C7~C 10 Aryl groups;
[0023] R”'3 and R”'4 may be the same or different, and each can be independently represented as C1 to C2. 14 Straight-chain alkyl groups, C3-C 14 Branched alkyl groups, C3-C 10 cycloalkyl, C6-C 10 aryl, C7~C 10 alkylaryl or C7~C 10 Aryl groups;
[0024] The magnesium element is derived from a magnesium-containing carrier, which includes the magnesium compound shown in formula (II);
[0025]
[0026] In formula (II), R1 is a straight-chain or branched alkyl group of C1 to C8, or a cycloalkyl group of C3 to C8;
[0027] R2 and R3 may be the same or different, and each is independently hydrogen or a straight-chain or branched alkyl group of C1 to C5, wherein the hydrogen on the alkyl group may optionally be replaced by a halogen atom; X is a halogen, preferably chlorine or bromine; m is 0.1 to 1.9, n is 0.1 to 1.9, and m+n=2.
[0028] According to a third aspect of the invention, the invention provides a catalyst for olefin polymerization, said catalyst comprising the solid catalyst component described in the second aspect of the invention, alkylaluminum, and optionally an external electron donor compound or its reaction product.
[0029] According to a fourth aspect of the present invention, the present invention provides a method for olefin polymerization, the method comprising: causing an olefin to undergo a polymerization reaction in the presence of the catalyst for olefin polymerization.
[0030] The catalyst described in this invention uses a specific magnesium-containing support. After prepolymerization using a special method, the catalyst's hydrogen sensitivity can be improved. At the same time, the polymer synthesized by the catalyst has a high bulk density and a wider molecular weight distribution, which is beneficial to improving the product's processing performance. Detailed Implementation
[0031] The present invention will be further described below with reference to specific embodiments, but this does not constitute any limitation on the present invention.
[0032] According to a first aspect of the present invention, the present invention provides a method for prepolymerizing a solid catalyst component, comprising:
[0033] (1) In the presence of an inert solvent, catalyst component A, alkylaluminum and an external electron donor compound are brought into contact and reacted; the catalyst component A comprises titanium, magnesium, halogen and an internal electron donor compound; the internal electron donor compound comprises the compound shown in formula (I);
[0034]
[0035] In equation (Ⅰ), R”'1 and R”'2 may be the same or different, and each is independently H, C1~C 14 Straight-chain alkyl groups, C3-C 14 Branched alkyl groups, C3-C 10 cycloalkyl, C6-C 10 aryl, C7~C 10 alkylaryl or C7~C 10 Aryl alkyl groups; R”'3 and R”'4 may be the same or different, and each is independently C1 to C4. 14 Straight-chain alkyl groups, C3-C 14 Branched alkyl groups, C3-C 10 cycloalkyl, C6-C 10 aryl, C7~C 10 alkylaryl or C7~C 10 Aryl group; wherein R”'1 and R”'2 are optionally bonded to each other to form one or more fused ring structures, and the hydrogen on the aromatic ring of the aryl, alkylaryl or aromatic group is optionally replaced by other atoms;
[0036] The magnesium element is derived from a magnesium-containing carrier, which includes the magnesium compound shown in formula (II);
[0037]
[0038] In formula (II), R1 is a C1-C8 straight-chain or branched alkyl group or a C3-C8 cycloalkyl group; R2 and R3 may be the same or different, each being independently hydrogen or a C1-C5 straight-chain or branched alkyl group, wherein the hydrogen on the alkyl group may optionally be replaced by a halogen atom; X is a halogen, preferably chlorine or bromine; m is 0.1-1.9, n is 0.1-1.9, and m+n=2;
[0039] (2) Add α-olefins to the reaction system obtained in step (1) to carry out a polymerization reaction;
[0040] (3) Remove the unreacted α-olefin from step (2) and add hydrogen to the reaction system obtained in step (2) to carry out the reaction.
[0041] According to the preparation method provided by the present invention, the method further includes: (4) removing unreacted hydrogen gas, and sequentially performing solid-liquid separation and drying on the system obtained in step (3) to obtain the solid catalyst component. In some preferred embodiments, the solid-liquid separation includes filtering to remove the liquid, followed by washing with hexane 1-2 times, and the drying process includes vacuum drying, wherein the drying conditions include a temperature of 10-80°C, preferably 40-50°C, and a time of 30-60 min. In the present invention, the vacuum drying can be carried out using a conventional vacuum pump, and the present invention has no special requirements for it.
[0042] Optionally, the inert solvent is selected from at least one of kerosene, paraffin oil, petrolatum oil, white oil, methyl silicone oil, ethyl silicone oil, methyl ethyl silicone oil, phenyl silicone oil, and methyl phenyl silicone oil.
[0043] Optionally, based on 1 mol of the magnesium compound shown in formula (II), the amount of the inert solvent is 0.8 to 10 L, preferably 2 to 8 L.
[0044] Optionally, the α-olefin is selected from one or more of ethylene, propylene, butene, octene and isopentene, preferably propylene.
[0045] Optionally, the mass ratio of the α-olefin to catalyst component A is 0.04:1 to 10:1. For example, the mass ratio of the α-olefin to catalyst component A can be 0.04:1, 0.05:1, 0.08:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, or a range thereof.
[0046] Optionally, in step (1), the conditions for the contact reaction include: a temperature of 0 to 30°C, preferably 15 to 25°C; and a time of 1 to 30 min, preferably 10 to 20 min.
[0047] Optionally, the conditions for the polymerization reaction in step (2) include: a temperature of 0 to 50°C, preferably 15 to 25°C; and a time of 5 to 30 minutes, preferably 10 to 20 minutes.
[0048] Optionally, the reaction conditions in step (3) include: a temperature of 0 to 50°C, preferably 15 to 25°C; and a time of 5 to 30 min, preferably 10 to 20 min.
[0049] Optionally, the amount of hydrogen added is controlled to maintain the reaction pressure at 0.01 to 1.0 MPa, preferably 0.1 to 0.5 MPa, and more preferably 0.2 to 0.3 MPa.
[0050] According to the preparation method provided by the present invention, in step (1), the alkylaluminum and the external electron donor compound can be selected from existing olefin prepolymerization catalysts, and the present invention does not particularly limit them. Typically, the alkylaluminum can be selected from one or more of triethylaluminum, triisobutylaluminum, tri-n-butylaluminum, tri-n-hexylaluminum, and diethylaluminum chloride. The external electron donor compound can be selected from one or more of cyclohexylmethyldimethoxysilane, diisopropyldimethoxysilane, n-butyldimethoxysilane, diisobutyldimethoxysilane, diphenyldimethoxysilane, methyl tert-butyldimethoxysilane, and dicyclopentyldimethoxysilane.
[0051] Generally, the molar ratio of the alkylaluminum, the external electron donor compound, and the catalyst component A (calculated as titanium) can be 1–50:0.2–10:1. For example, the molar ratio of the alkylaluminum, the external electron donor compound, and the catalyst component A (calculated as titanium) can be any range of values for alkylaluminum and the external electron donor compound within the ranges of 1:0.2:1, 5:0.2:1, 10:0.2:1, 15:0.2:1, 20:0.2:1, 30:0.2:1, 40:0.2:1, 50:0.2:1, 15:0.3:1, 15:0.5:1, 15:1:1, 15:2:1, 15:3:1, 15:4:1, 15:5:1, 15:20:1, or higher.
[0052] According to the preparation method provided by the present invention, in step (1), the inert solvent can be selected with reference to the prior art. Generally, the inert solvent can be one or more of hexaane, heptane, and decane. The amount of inert solvent added is such that the mass concentration of catalyst component A in the inert solvent can be 5 to 50 g / L.
[0053] According to the preparation method provided by the present invention, hydrogen gas can be added in the form of pure hydrogen gas or a hydrogen gas mixture. Preferably, the hydrogen gas mixture is composed of hydrogen gas and an inert gas; more preferably, the inert gas is selected from at least one of nitrogen, helium, neon, and argon. The present invention does not have special requirements on the concentration of hydrogen gas in the hydrogen gas mixture, as long as the defined reaction pressure can be achieved.
[0054] According to the preparation method provided by the present invention, the catalyst component A can be prepared by conventional methods for main catalysts in olefin polymerization catalysts in the art. The present invention does not particularly limit this, for example, it can be prepared by referring to the methods disclosed in patent applications WO2012034357A1, WO2012097680A1 and patents ZL03153152.0, ZL200410062291.3, ZL201310491641.7, ZL201310491393.6 and ZL201310491648.9.
[0055] Specifically, catalyst component A may include titanium tetrachloride, a magnesium-containing support, and the reaction product of an internal electron donor compound such as a carboxylic acid ester, wherein the magnesium-containing support is a spherical magnesium compound support.
[0056] In this invention, the average particle size of the magnesium-containing carrier is 5–150 μm, preferably 20–80 μm, and more preferably 30–60 μm.
[0057] According to the preparation method provided by the present invention, the vacuum drying conditions in the above operations include: a temperature of 40–50°C and a time of 30–60 min. In this invention, the vacuum drying can be carried out using a conventional vacuum pump, and there are no special requirements for it.
[0058] According to a second aspect of the present invention, the present invention provides a solid catalyst component for olefin polymerization prepared by the prepolymerization method described in the first aspect of the present invention, comprising magnesium, titanium, halogen, poly-α-olefin and an internal electron donor compound, wherein the internal electron donor compound comprises the compound shown in formula (I);
[0059]
[0060] In equation (Ⅰ), R”'1 and R”'2 may be the same or different, and each is independently H, C1~C14 Straight-chain alkyl groups, C3-C 14 Branched alkyl groups, C3-C 10 cycloalkyl, C6-C 10 aryl, C7~C 10 alkylaryl or C7~C 10 Aryl groups;
[0061] R”'3 and R”'4 may be the same or different, and each can be independently represented as C1 to C2. 14 Straight-chain alkyl groups, C3-C 14 Branched alkyl groups, C3-C 10 cycloalkyl, C6-C 10 aryl, C7~C 10 alkylaryl or C7~C 10 Aryl groups;
[0062] Wherein, R”'1 and R”'2 are optionally bonded to each other to form one or more fused ring structures, and the hydrogen on the aromatic ring of the aryl, alkylaryl or aromatic group is optionally replaced by other atoms;
[0063] The magnesium element is derived from a magnesium-containing carrier, which includes the magnesium compound shown in formula (II);
[0064]
[0065] In formula (II), R1 is a straight-chain or branched alkyl group of C1 to C8, or a cycloalkyl group of C3 to C8;
[0066] R2 and R3 may be the same or different, and each is independently hydrogen or a straight-chain or branched alkyl group of C1 to C5, wherein the hydrogen on the alkyl group may optionally be replaced by a halogen atom; X is a halogen, preferably chlorine or bromine; m is 0.1 to 1.9, n is 0.1 to 1.9, and m+n=2.
[0067] Optionally, the polyalphaolefin is selected from one or more of polyethylene, polypropylene, polybutene, polyoctene and polyisoprene, preferably polypropylene.
[0068] Optionally, based on the total weight of the solid catalyst components, the solid catalyst components contain 1-18% by weight of magnesium, 0.1-3.5% by weight of titanium, 2-65% by weight of halogens, 0.1-89% by weight of poly-α-olefins, and 0.6-15% by weight of internal electron donor compounds.
[0069] In some embodiments, based on the total mass of the solid catalyst component, the solid catalyst component contains 0.1–89 wt% polyalphaolefin, 0.1–3.5 wt% titanium, 1–18 wt% magnesium, 2–65 wt% chlorine, and 0.6–15 wt% internal electron donor compound. Preferably, based on the total weight of the solid catalyst component, the content of polyalphaolefin is 1–50 wt%, the content of titanium is 0.5–2.5 wt%, the content of magnesium is 1–16 wt%, the content of chlorine is 2–55 wt%, and the content of internal electron donor compound is 1–10 wt%.
[0070] In some embodiments, based on the total weight of the solid catalyst components, the content of the poly-α-olefin is 9.5–35 wt%, the content of titanium is 1.5–2.5 wt%, the content of magnesium is 11–16 wt%, the content of chlorine is 40–55 wt%, and the content of the internal electron donor compound is 8–10 wt%.
[0071] Optionally, the halogen in this invention is selected from one or more of fluorine, chlorine, bromine and iodine, preferably chlorine.
[0072] Optionally, the solid catalyst component is spherical solid particles.
[0073] Optionally, the average particle size D of the solid catalyst component 50 The particle size is 5–150 μm, preferably 20–80 μm. For example, the average particle size D of the solid catalyst component... 50 It can be 5μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 100μm, 120μm, 150μm or a range thereof.
[0074] In this invention, the average particle size D 50 The particle size distribution was measured using a Master Sizer 2000 laser particle size analyzer (manufactured by Malvern Instruments Ltd).
[0075] According to the solid catalyst composition provided by the present invention, the titanium content can be determined by colorimetry. Specifically, 0.2-0.5 g of sample is dissolved in 50 mL of 2N H2SO4, the supernatant is filtered, and the clear liquid is collected for colorimetric analysis. Using 2N H2SO4 solution as a blank, with a cuvette thickness of 1 cm, the absorbance E1 is measured at a wavelength of 410 μm. Then, 1 drop of 30% H2O2 is added, shaken well, and the absorbance E2 is measured. The titanium content Ti (%) is calculated according to the following formula:
[0076] Ti%=[(E2-E1)×100) / (K·L·W·100)]×100
[0077] Where: W—sample weight (g); L—cuvette thickness (cm); K—specific extinction coefficient; E1—blank absorbance; E2—sample absorbance.
[0078] Magnesium content can be determined by EDTA titration. Specifically, take 0.2-0.5g of sample into a 250mL Erlenmeyer flask, add 20-30mL of 2N H2SO4 solution to dissolve, add 20mL of triethanolamine (1+2) standard solution, adjust the pH to 10 with 20% NaOH solution, shake, add 10mL of pH 10 buffer solution, then add 6 drops of 30% H2O2 and 30-50mL of distilled water, add a small amount of Eriochrome Black T indicator, shake well, and titrate with 0.02N EDTA solution until the color changes from purple-red to blue (violet light disappears) as the endpoint. Calculate the magnesium content (Mg) using the following formula:
[0079] Mg(%)=[(VE·NE×24.31) / (G·1000)]×100
[0080] Where: G—sample mass (g); VE—amount of EDTA consumed (mL); NE—equivalent number of EDTA solution; 24.31—atomic weight of magnesium.
[0081] The chlorine content can be determined by silver nitrate titration. Specifically, weigh 0.04-0.1g of sample into an Erlenmeyer flask, add 20mL of 2N H2SO4 solution, and let stand for 30 minutes. After rinsing several times with distilled water, add 20-30mL of 0.1N AgNO3 solution, then add 3mL of 1:1 HNO3 solution. Titrate the excess AgNO3 solution with 0.1N NH4CNS standard solution until the brick-red color persists for two seconds. Calculate the chlorine content (Cl%) using the following formula:
[0082] Cl(%)=[(V1-V2×D)×N1×35.45 / G·1000)]×100
[0083] In the formula: V1—volume of AgNO3 solution (mL); V2—volume of NH4CNS solution consumed (mL); D—volume ratio of AgNO3 / NH4CNS solution; N1—equivalent concentration of AgNO3; G—mass of sample (g); 35.45—atomic weight of chlorine.
[0084] The method for testing the polyalphaolefin content in the solid catalyst component is as follows: A certain amount (M1) of sample is weighed and dissolved in ethanol and dilute hydrochloric acid. The insoluble matter is dried under vacuum at 80℃ to obtain a solid (M2). 0.2g of the solid is pressed into a tablet, and the polyalphaolefin content (C1) of the solid is measured using an infrared spectrometer. The mass percentage of polyalphaolefin in the solid catalyst component is calculated according to the following formula:
[0085] C A =M2×C1 / M1
[0086] C A C1 represents the mass percentage of poly-α-olefin in the solid catalyst component, M1 and M2 represent the mass (g) of the sample and the dried solid, respectively, and C1 represents the mass percentage of poly-α-olefin in the dried solid.
[0087] The method for testing the content of internal electron donor compounds in solid catalyst components is as follows: the sample is dissolved in ethyl acetate and hydrochloric acid solution (concentration 2 mol / L), and the internal electron donor compounds are extracted and their content is analyzed using conventional liquid chromatography.
[0088] The solid catalyst composition provided by the present invention further comprises alkyl aluminum and an external electron donor. The type and content of the alkyl aluminum and the external electron donor can be selected with reference to existing olefin prepolymerization catalysts.
[0089] In addition, the solid catalyst components of the present invention may contain other components besides the above-mentioned components, such as inert solvents.
[0090] According to a third aspect of the invention, the present invention provides a catalyst for olefin polymerization, the catalyst comprising a solid catalyst component prepared by the prepolymerization method described herein, and alkylaluminum and optionally an external electron donor compound or a reaction product thereof.
[0091] According to the catalyst provided by the present invention, the alkylaluminum, the external electron donor compound, and their respective contents can be selected according to the prior art.
[0092] Generally, the alkylaluminum may be selected from one or more of triethylaluminum, triisobutylaluminum, tri-n-butylaluminum, tri-n-hexylaluminum, and diethylaluminum chloride.
[0093] The molar ratio of the alkylaluminum (calculated as aluminum) to the molar ratio of the solid catalyst component (calculated as titanium) can be 1 to 1000:1. For example, the molar ratio of the alkylaluminum (calculated as aluminum) to the molar ratio of the solid catalyst component (calculated as titanium) can be 1:1, 2:1, 5:1, 10:1, 20:1, 50:1, 100:1, 200:1, 500:1, 1000:1, or a range thereof.
[0094] Generally, the external electron donor compound may be selected from at least one of cyclohexylmethyldimethoxysilane, diisopropyldimethoxysilane, di-n-butyldimethoxysilane, diisobutyldimethoxysilane, diphenyldimethoxysilane, methyl-tert-butyldimethoxysilane, dicyclopentyldimethoxysilane, cyclohexyltrimethoxysilane, tert-butyltrimethoxysilane, and tert-hexyltrimethoxysilane.
[0095] The molar ratio of the alkylaluminum (calculated as aluminum) to the molar ratio of the external electron donor compound (calculated as silicon) is 2 to 1000:1. For example, the molar ratio of the alkylaluminum (calculated as aluminum) to the molar ratio of the external electron donor compound (calculated as silicon) can be 2:1, 5:1, 10:1, 20:1, 50:1, 100:1, 200:1, 500:1, 1000:1, or a range thereof.
[0096] According to a fourth aspect of the present invention, the present invention provides a method for olefin polymerization, the method comprising: subjecting an olefin to a polymerization reaction in the presence of a catalyst for olefin polymerization as described in a third aspect of the present invention.
[0097] According to the method provided by the present invention, the olefin has the general formula CH2=CHR, where R is hydrogen, a C1-C6 alkyl group, or a C6-C6 alkyl group. 10 The aryl group. Preferably, the olefin is selected from one or more of ethylene, propylene, butene, pentene, and hexene.
[0098] According to the method provided by the present invention, the conditions of the polymerization reaction can be conventionally selected in the art, such as a reaction temperature of 0 to 150°C, preferably 60 to 90°C, and a reaction pressure of atmospheric pressure or higher.
[0099] The advantages of the technical solution of the present invention will be described in detail below through specific embodiments.
[0100] In the following examples and comparative examples,
[0101] The isotactic index of a polymer (polypropylene) refers to the percentage by mass of the polymer that is insoluble in boiling heptane under specified conditions. It is determined by the heptane extraction method (boiling heptane extraction for 6 hours). Specifically, 2g of dried polymer sample is placed in an extractor and extracted with boiling heptane for 6 hours. The residue is then dried to constant weight. The ratio of the mass (g) of the obtained polymer to 2 is the isotactic index.
[0102] The polymer melt index was determined according to the method of ASTM D1238-99.
[0103] In the following embodiments, unless otherwise specified, "vacuum" refers to the vacuum level achieved by a conventional vacuum pump.
[0104] The following preparation examples illustrate the preparation method of catalyst component A.
[0105] Preparation Example 1
[0106] In a 2L reactor, 40g (0.4mol) magnesium chloride, 280mL (4.8mol) ethanol, 5g ethyl acetate, and 5g PVP (polyvinylpyrrolidone) were added as surfactants. The mixture was heated to 90℃ with stirring and reacted at a constant temperature for 2 hours. Then, 190mL (2.4mol) epichlorohydrin was added and the reaction was continued at 90℃ for another half hour. The mixture was then filtered under pressure. The filtered product was washed eight times with toluene and finally dried under vacuum to obtain spherical support Z1 for olefin polymerization catalyst.
[0107] The average particle diameter (D50) of the spherical support Z1 for olefin polymerization catalyst is 56 micrometers, and the particle size distribution ((D90-D10) / D50) is 1.0. Optical microscopy revealed that the spherical support Z1 for olefin polymerization catalyst has a relatively regular particle morphology, a smooth surface, and is almost entirely spherical with a concentrated particle size distribution and virtually no irregularly shaped particles.
[0108] Based on gas chromatography-mass spectrometry, elemental analysis, and NMR characterization, the structural formula of Z1 is:
[0109]
[0110] In a 2.5 L glass reaction flask, 500 mL of titanium tetrachloride was added and cooled to -20 °C. 40 g of the spherical support Z1 for the olefin polymerization catalyst obtained in Preparation Example 1 was then added, and the mixture was stirred at -20 °C for 30 min. The temperature was then slowly increased to 110 °C, and 7.5 mL of diethyl 2,3-diisopropyl-2-cyanobutane was added during the heating process. The mixture was maintained at 110 °C for 30 min, and the liquid was filtered off. The mixture was then washed twice with titanium tetrachloride, and finally washed three times with hexane. After drying, the olefin polymerization catalyst A-1 was obtained.
[0111] Preparation Example 2
[0112] In a 2L reactor, 40g (0.4mol) magnesium chloride, 280mL (4.8mol) ethanol, 5g ethyl acetate, and 5g PVP (polyvinylpyrrolidone) were added as surfactants. The mixture was heated to 90℃ with stirring and reacted at a constant temperature for 2 hours. Then, 1.6mol epichlorohydrin was added and the reaction was continued at 90℃ for another 30 hours. The mixture was then filtered under pressure. The filtered product was washed 8 times with toluene and finally dried under vacuum to obtain Z2, a spherical support for olefin polymerization catalyst.
[0113] The average particle diameter (D50) of the spherical support Z2 for olefin polymerization catalyst is 50 micrometers, and the particle size distribution ((D90-D10) / D50) is 1.0. Optical microscopy revealed that the spherical support Z2 for olefin polymerization catalyst has a relatively regular particle morphology, a smooth surface, and is almost entirely spherical with a concentrated particle size distribution and virtually no irregularly shaped particles.
[0114] Based on gas chromatography-mass spectrometry, elemental analysis, and NMR characterization, the structural formula of Z2 is:
[0115] In a 2.5L glass reaction flask, add 500mL of titanium tetrachloride, cool to -20℃, and then add 40g of...
[0116] The spherical support Z2 of the olefin polymerization catalyst obtained in Preparation Example 2 was added and stirred at -20°C for 30 min. Then, the temperature was slowly increased to 110°C, and 7.5 mL of diethyl 2,3-diisopropyl-2-cyanobutanoate was added during the heating process. The mixture was maintained at 110°C for 30 min, and then the liquid was filtered off. The catalyst was then washed twice with titanium tetrachloride, and finally three times with hexane. After drying, olefin polymerization catalyst A-2 was obtained.
[0117] The following examples illustrate the solid catalyst components and their preparation methods of the present invention, as well as the method for olefin polymerization.
[0118] Example 1
[0119] (1) Preparation of solid catalyst components
[0120] In a 5L autoclave, 1.1L of hexane, 15mmol of triethylaluminum, 0.3mmol of cyclohexylmethyldimethoxysilane, and 20.0g of catalyst component A-1 were added and reacted at 22°C for 10 minutes. Then, 10g of propylene was added, and the reaction was carried out at 20°C for 10 minutes, after which unreacted propylene was vented. The autoclave was then purged with nitrogen, and hydrogen was added to a reaction pressure of 0.2MPa. The reaction was carried out at 15°C for 10 minutes, after which unreacted hydrogen was vented. The liquid in the reaction product was filtered off, and the product was dried under vacuum (45°C for 40 minutes) to obtain a solid catalyst component, denoted as E-1.
[0121] (2) Propylene Polymerization A
[0122] In a 5L autoclave, 1.3 mmol of triethylaluminum, 0.05 mmol of cyclohexylmethyldimethoxysilane, 10 mL of hexane and 15 mg of solid catalyst component E-1 were added. After purging with 1.5 NL of hydrogen gas, 2.0 L of liquid propylene was added. The temperature was raised to 70 °C under stirring and the polymerization reaction was carried out at 70 °C for 1 hour. After stirring was stopped, the unpolymerized propylene monomer was removed to obtain polypropylene, denoted as P-1A.
[0123] Propylene Polymer B
[0124] Propylene polymerization is performed using method A, except that 6.5 NL of hydrogen gas is added, denoted as P-1B.
[0125] Example 2
[0126] (1) Preparation of solid catalyst components
[0127] In a 5L autoclave, 1.0L of hexane, 15mmol of triethylaluminum, 0.3mmol of cyclohexylmethyldimethoxysilane, and 20.0g of catalyst component A-2 were added, and the reaction was carried out at 15°C for 10 minutes. Then, 12g of propylene was added, and the reaction was carried out at 25°C for 10 minutes, after which unreacted propylene was vented. The autoclave was then purged with nitrogen, and hydrogen was added to a reaction pressure of 0.2MPa. The reaction was carried out at 20°C for 10 minutes, after which unreacted hydrogen was vented. After filtering off the liquid from the reaction product, the product was dried under vacuum to obtain a solid catalyst component, denoted as E-2.
[0128] (2) Propylene Polymerization A
[0129] Polymerization was carried out according to the propylene polymerization method of Example 1, with E-2 replacing E-1, to obtain polypropylene, denoted as P-2A.
[0130] Propylene Polymer B
[0131] Propylene polymerization is performed using method A, except that 6.5 NL of hydrogen gas is added, denoted as P-2B.
[0132] Example 3
[0133] (1) Preparation of solid catalyst components
[0134] In a 5L autoclave, 1.0L of hexane, 15mmol of triethylaluminum, 0.3mmol of cyclohexylmethyldimethoxysilane, and 20.0g of catalyst component A-2 were added, and the reaction was carried out at 15°C for 10 minutes. Then, 12g of ethylene was added, and the reaction was carried out at 30°C for 10 minutes, after which unreacted propylene was vented. The autoclave was then purged with nitrogen, and hydrogen was added to a reaction pressure of 0.2MPa. The reaction was carried out at 25°C for 10 minutes, after which unreacted hydrogen was vented. After filtering off the liquid from the reaction product, the product was dried under vacuum to obtain a solid catalyst component, denoted as E-3.
[0135] (2) Propylene Polymerization A
[0136] Polymerization was carried out according to the propylene polymerization method of Example 1, with E-3 replacing E-1, to obtain polypropylene, denoted as P-3A.
[0137] Propylene Polymer B
[0138] Propylene polymerization is performed using method A, except that 6.5 NL of hydrogen gas is added, denoted as P-3B.
[0139] Comparative Example 1
[0140] Propylene Polymerization A
[0141] The method of propylene polymerization A and B in Example 1 is followed, except that catalyst component A-1 is used instead of E-1 to obtain polypropylene, denoted as CP-1A and CP-1B.
[0142] Comparative Example 2
[0143] Propylene Polymerization A
[0144] The method of propylene polymerization A and B in Example 2 is followed, except that catalyst component A-2 is used instead of E-2 to obtain polypropylene, denoted as CP-2A and CP-2B.
[0145] Comparative Example 3
[0146] The method of Preparation Example 1 was followed, except that 2,4-pentanediol dibenzoate was used instead of 2,3-diisopropyl-2-cyanosuccinate diethyl ester to obtain the catalyst component, denoted as 2A-1.
[0147] Following the catalyst preparation method of Example 1, a catalyst component was obtained, denoted as 2E-1.
[0148] The method of propylene polymerization A and B in Example 1 is followed, except that 2A-1 and 2E-1 are used instead of E-1 to obtain polypropylene, which are denoted as 2PA-1A and 2PA-1B, 2PE-1A and 2PE-1B, respectively.
[0149] Table 1. Propylene polymerization results
[0150]
[0151]
[0152] As can be seen, the solid catalyst component of the present invention, when used for olefin polymerization, significantly improves the hydrogen sensitivity of the catalyst compared with existing prepolymerization catalyst technologies, such as compared with the comparative example. Moreover, the bulk density of the propylene polymer is also significantly improved, and the molecular weight distribution is significantly broadened, which is more conducive to resin processing.
[0153] Any numerical value mentioned in this invention, if there is only a two-unit interval between any minimum and any maximum value, includes all values that increase by one unit each time from the minimum to the maximum value. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, or time, is stated as 50-90, in this specification it means specifically listing values such as 51-89, 52-88… and 69-71 and 70-71, etc. For non-integer values, it may be appropriately considered that a unit is 0.1, 0.01, 0.001, or 0.0001. These are merely some specifically specified examples. In this application, in a similar manner, all possible combinations of numerical values between the listed minimum and maximum values are considered to have been disclosed.
[0154] It should be noted that the embodiments described above are only for explaining the present invention and do not constitute any limitation on the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory terms, not limiting terms. Modifications can be made to the present invention within the scope of the claims, and revisions can be made to the present invention without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials, and embodiments, it does not mean that the present invention is limited to the specific examples disclosed herein; on the contrary, the present invention can be extended to all other methods and applications with the same function.
Claims
1. A method for prepolymerizing a solid catalyst component, characterized in that, include: (1) In the presence of an inert solvent, catalyst component A, alkylaluminum and external electron donor compound are brought into contact and reacted; the catalyst component A contains titanium, magnesium, halogen and internal electron donor compound; the internal electron donor compound includes the compound shown in formula (I); Equation (I) In equation (Ⅰ), R'''1 and R'''2 may be the same or different, and each is independently H, C1~C 14 Straight-chain alkyl, C3~C 14 Branched alkyl groups, C3~C 10 cycloalkyl, C6~C 10 aryl, C7~C 10 alkylaryl or C7~C 10 Aryl alkyl groups; R'''3 and R'''4 may be the same or different, and each is independently C1~C4. 14 Straight-chain alkyl, C3~C 14 Branched alkyl groups, C3~C 10 cycloalkyl, C6~C 10 aryl, C7~C 10 alkylaryl or C7~C 10 Aryl group; wherein R'''1 and R'''2 are optionally bonded to each other to form one or more fused ring structures, and the hydrogen on the aromatic ring of the aryl, alkylaryl or aromatic group is optionally replaced by other atoms; The magnesium element is derived from a magnesium-containing carrier, which includes the magnesium compound shown in formula (II); (Ⅱ) In formula (II), R1 is a C1~C8 straight-chain or branched alkyl group or a C3~C8 cycloalkyl group; R2 and R3 may be the same or different, and each is independently hydrogen or a C1~C5 straight-chain or branched alkyl group, wherein the hydrogen on the alkyl group may be optionally replaced by a halogen atom; X is a halogen; m is 0.1~1.9, n is 0.1~1.9, and m+n=2; (2) Add α-olefins to the reaction system obtained in step (1) to carry out a polymerization reaction; (3) Remove the unreacted α-olefin from step (2) and add hydrogen to the reaction system obtained in step (2) to carry out the reaction; (4) Remove unreacted hydrogen gas, and sequentially perform solid-liquid separation and drying on the system obtained in step (3) to obtain solid catalyst components. The drying conditions include: temperature of 10-80℃ and time of 30-60min. In step (1), the conditions for the contact reaction include: a temperature of 0~30℃ and a time of 1~30min; In step (2), the mass ratio of the α-olefin to catalyst component A is 0.1:1 to 1:1, and the conditions for the polymerization reaction include: temperature of 0 to 50°C and time of 5 to 30 min. The reaction conditions in step (3) include: a temperature of 0~50℃, a time of 5~30min; and controlling the amount of hydrogen added to maintain the reaction pressure at 0.01~1.0MPa.
2. The prepolymerization method according to claim 1, characterized in that, In formula (II), X is chlorine or bromine.
3. The prepolymerization method according to claim 1 or 2, characterized in that, The average particle size of the magnesium-containing carrier is 5~150μm.
4. The prepolymerization method according to claim 3, characterized in that, The average particle size of the magnesium-containing carrier is 20~80μm.
5. The prepolymerization method according to claim 4, characterized in that, The average particle size of the magnesium-containing carrier is 30~60μm.
6. The prepolymerization method according to claim 1 or 2, characterized in that, The inert solvent is selected from at least one of hexane, kerosene, paraffin oil, petrolatum oil, white oil, methyl silicone oil, ethyl silicone oil, methyl ethyl silicone oil, phenyl silicone oil, and methyl phenyl silicone oil. And / or, based on 1 mol of the magnesium compound shown in formula (II), the amount of the inert solvent is 0.8 to 10 L.
7. The prepolymerization method according to claim 6, characterized in that, Based on 1 mol of the magnesium compound shown in formula (II), the amount of the inert solvent used is 2~8 L.
8. The prepolymerization method according to claim 1 or 2, characterized in that, The α-olefin is selected from one or more of ethylene, propylene, butene, octene, and isopentene; And / or, the mass ratio of the α-olefin to catalyst component A is 0.3:1 to 0.8:
1.
9. The prepolymerization method according to claim 1 or 2, characterized in that, The reaction conditions described in step (3) include: a temperature of 15~25℃; and a time of 10~20min; And / or, control the amount of hydrogen added to maintain the reaction pressure at 0.1~0.5 MPa.
10. The prepolymerization method according to claim 9, characterized in that, In step (1), the conditions for the contact reaction include: a temperature of 15~25℃ and a time of 10~20min; And / or, the conditions for the polymerization reaction described in step (2) include: a temperature of 15~25℃; and a time of 10~20min; And / or, in step (3), the amount of hydrogen added is controlled to maintain the reaction pressure at 0.2~0.3 MPa.
11. A solid catalyst component prepared by the prepolymerization method according to any one of claims 1 to 10.
12. The solid catalyst component according to claim 11, characterized in that, It includes magnesium, titanium, halogens, polyalphaolefins, and internal electron donor compounds; the internal electron donor compounds include compounds shown in formula (I); Equation (I) In equation (Ⅰ), R'''1 and R'''2 may be the same or different, and each is independently H, C1~C 14 Straight-chain alkyl, C3~C 14 Branched alkyl groups, C3~C 10 cycloalkyl, C6~C 10 aryl, C7~C 10 alkylaryl or C7~C 10 Aryl groups; R'''3 and R'''4 may be the same or different, and each can be independently represented as C1~C1. 14 Straight-chain alkyl, C3~C 14 Branched alkyl groups, C3~C 10 cycloalkyl, C6~C 10 aryl, C7~C 10 alkylaryl or C7~C 10 Aryl groups; In this configuration, R'''1 and R'''2 are optionally bonded to each other to form one or more fused ring structures, and the hydrogen atoms on the aromatic rings of the aryl, alkylaryl, or aromatic group are optionally replaced by other atoms.
13. The solid catalyst component according to claim 12, characterized in that, The polyα-olefin is selected from one or more of polyethylene, polypropylene, polybutene, polyoctene, and polyisoprene; And / or, based on the total weight of the solid catalyst components, the solid catalyst components contain 1-18% by weight of magnesium, 0.1-3.5% by weight of titanium, 2-65% by weight of halogens, 0.1-89% by weight of polyalphaolefins, and 0.6-15% by weight of internal electron donor compounds; And / or, the solid catalyst component is spherical solid particles; And / or, the average particle size D of the solid catalyst component 50 The range is 5~150μm.
14. The solid catalyst component according to claim 13, characterized in that, Based on the total weight of the solid catalyst components, the solid catalyst components contain 1-50% by weight of polyα-olefin, 0.5-2.5% by weight of titanium, 1-16% by weight of magnesium, 2-55% by weight of halogens, and 1-10% by weight of internal electron donor compounds. And / or, the average particle size D of the solid catalyst component 50 The size is 20~80μm.
15. The solid catalyst component according to claim 14, characterized in that, Based on the total weight of the solid catalyst components, the solid catalyst components contain 9.5-35% by weight of poly-α-olefin, 1.5-2.5% by weight of titanium, 11-16% by weight of magnesium, 40-55% by weight of halogens, and 8-10% by weight of internal electron donor compounds.
16. A catalyst for olefin polymerization, characterized in that, The catalyst comprises a solid catalyst component, alkyl aluminum and optional external electron donor compound or its reaction product; The solid catalyst component is selected from at least one of the solid catalyst components according to any one of claims 11 to 15 and the solid catalyst components prepared by the prepolymerization method according to any one of claims 1 to 10.
17. A method for olefin polymerization, characterized in that, The method includes: polymerizing an olefin in the presence of the catalyst for olefin polymerization as described in claim 16.
18. The method for olefin polymerization according to claim 17, characterized in that, The olefin has the general formula CH2=CHR, where R is hydrogen, a C1-C6 alkyl group, or a C6-C6 alkyl group. 10 Aryl groups.
19. The method for olefin polymerization according to claim 17, characterized in that, The polymerization reaction is carried out at a temperature of 0~150℃.
20. The method for olefin polymerization according to claim 19, characterized in that, The polymerization reaction is carried out at a temperature of 60~90℃.
Citation Information
Patent Citations
A spherical carrier for olefin polymerization catalyst and preparation method thereof
CN104558281B
A solid composition, its preparation method and application
CN104558283B
Catalyst component used for olefin polymerization and preparation method thereof as well as catalyst used for olefin polymerization and application
CN104558284A
Olefin polymerization catalyst support, preparation method, catalyst component for olefin polymerization, olefin polymerization catalyst and applications of olefin polymerization catalyst support, catalyst component for olefin polymerization and olefin polymerization catalyst
CN107915795A
Globular catalyst component used for olefine polymerization and its catalyst
CN1289542C